Long-wave infrared radiation properties of vertical green façades in subtropical regions. (September 2022) - Zhao, Cheng; Zhang, Lei; Yang, Yuanqin; Zhang, Yu; Liu, Mingxin; Yan, Junru; Zhao, Lihua
Abstract: Applying vertical green facades (VGFs) on building envelopes is an effective design strategy to reduce building energy consumption and mitigate the urban heat island effect. Although many studies have investigated the cooling and energy-saving effects of VGFs, research on the long-wave infrared radiation properties of VGFs remains scarce, limiting the understanding and application of heat-transfer models of VGFs. Therefore, in this study, theoretical analyses and field measurements were performed in the subtropical city of Guangzhou, China, to examine the long-wave infrared radiation properties of VGFs. First, an observation platform was established using six plants commonly used for VGFs in subtropical regions. The long-wave infrared radiation and leaf temperature of these plants with different coverage rates were measured to investigate the effect of coverage rate on the radiation transfer of the vegetation canopy. A Fourier spectrometer was used to analyse the spectral features of the leaves in the long-wave infrared radiation band. Based on the observation data and radiation balance of the vegetation canopy, an empirical equation for transmitting long-wave infrared radiation was established. Moreover, the monthly variations in the leaf area index and coverage rate of the VGFs were recorded throughout 2021, and an exponential function was used to determine the relationship between them. A quantitative method was used to assess the accuracy of the long-wave infrared radiation model, and the results indicated that the calculated values were in good agreement with the measured values. Highlights: Long-wave infrared radiation properties of VGFs were investigated. Experimental data were collected to fit the ambient equivalent temperature. The long-wave infrared radiation transfer in an uneven canopy was modelled. The correspondence between the coverage rate and the LAI was found.